Functionalisation and immobilisation of an Au(110) surface via uracil and 2-thiouracil anchored layer. Issue 23 (21st June 2015) - Plekan, Oksana; Feyer, Vitaliy; Cassidy, Andrew; Lyamayev, Victor; Tsud, Nataliya; Ptasińska, Sylwia; Reiff, Sara; Acres, Rober G.; Prince, Kevin C.
<x xml:space="preserve">Abstract</x> We conducted studies on surface functionalisation by uracil and 2-thiouracil, and immobilisation of several DNA moieties on functionalised gold surfaces.